(3EOGQI GdehGQO GdHTQjI (B/s - (3MShfI, ajUds ((3YeGf(B: s (3OGQ CSGeI ddfTQ hGdJhRjY(B, s, 2011)
(3jVe EOGQI GdehGQO GdHTQjI, GdJejR aj EOGQI GdehGQO GdHTQjI, JNWjW GdGMJjGLGJ ef GdehGQO GdHTQjI, GdGNJjGQ hGdJhXja, cja JMaR GdehGWfjf, GdCLhQ hGdQhGJH, GdQbGHI, JfejI GdehGQO GdHTQjI, eTGcd GdYGedjf, EYOGO ehGRfI bSe GdehGQO GdHTQjI, JCKjQ GdJhXja Ydi GdefXeI, efM GdUdGMjGJ, OhQ GdehGQO GdHTQjI aj GdJfejI GdGbJUGOjI, cjajI JCSjS bSe ehGQO GdHTQjI hJhbYGJgG aj GdCdajI GdKGdKI, GdJSjH GdEOGQj, EYOGO Gdbhi GdYGedI deLJeY GdeYdheGJ, GdCfaLGQ GdeYQaj hNjGQ GdehGQO GdHTQjI(B.s
(3HjHdjhZQGajG(B: (3U U(B.317-320s
Keywords: (3EOGQI GdCYeGds; (3EOGQI GdCaQGOs; (3GdEOGQIs